Knockdown of MKL1 ameliorates oxidative stress-induced chondrocyte apoptosis and cartilage matrix degeneration by activating TWIST1-mediated PI3K/AKT signaling pathway in rats - Chao Wan; Wei Liu; Limin Jiang; Shengjie Dong; Weihua Ma; Shijun Wang; Dan Liu (Taylor & Francis Group, 2022)
Studies have reported that megakaryocytic leukemia 1 (MKL1) is closely related to the pathological process of a variety of inflammatory diseases, but its role in osteoarthritis (OA) needs to be clarified. This study aimed to investigate the regulatory role of MKL1 in oxidative stress-induced chondrocyte apoptosis and cartilage matrix degeneration. The expressions of target mRNAs and proteins were measured by using reverse transcription-quantitative polymerase chain reaction and western blotting. ELISA assay was used to measure the levels of IL-6, IL-8, and TNF-α in chondrocytes. And commercial kits based on different spectrophotometry or colorimetry methods were performed to validate oxidative stress. CCK-8 and apoptosis kits were used to determine cell viability and apoptosis. Rat OA model was established by anterior cruciate ligament transection (ACLT), and the expression of MKL1 was interfered by injecting sh-MKL1 lentiviral vector into caudal vein. The results showed that the expression of MKL1was induced by H2O2 in chondrocytes. Knockdown of MKL1 alleviated H2O2-induced inflammation and cell apoptosis, reduced H2O2-induced oxidative stress, and improved cartilage matrix degeneration of chondrocytes. Besides, inhibition of MKL1 regulated the activation of TWIST1-mediated PI3K/AKT signaling. Further studies have found that TWIST1-mediated PI3K/AKT signaling was involved in the regulation mechanism of MKL1 on chondrocyte apoptosis and cartilage matrix degeneration. Next, intervention with MKL1 inhibited the progression of OA in rats. These results demonstrated that MKL1 regulate the apoptosis and cartilage matrix degeneration of chondrocytes via TWIST1-mediated PI3K/AKT signaling.